INOVASI PEMBELAJARAN NAHWU WADHIH: INTEGRASI WORDWALL DAN ACTIVE LEARNING DI PONDOK PESANTREN AL ITTIFAQIAH - Jumitria, Jumitria; Jumhur, Jumhur; Rendi Sabana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The learning of Nahwu requires an interactive approach to enable students to understand i‘rab rules easily and functionally. Traditional lecture and rote memorization methods make students passive and result in suboptimal learning outcomes. This study aims to examine the implementation of Nahwu Wadhih learning innovation through the integration of Word Wall media and Active Learning methods at Pondok Pesantren Al-Ittifaqiah, describe the changes in the learning process, and analyze improvements in students’ understanding and engagement. The research employed a mixed methods approach, combining qualitative data from observations, interviews, and documentation with quantitative data from pre-tests, post-tests, and Likert-scale questionnaires. Data analysis included descriptive statistics, normality tests, Paired Sample t-tests, and N-Gain calculations. The results indicate that before the intervention, learning was dominated by lectures and memorization, with a pre-test average score of 65.75. After implementing Word Wall and Active Learning, students became more active, collaborative, and able to apply Nahwu rules, as reflected in a post-test average of 80.56. Paired Sample t-test results showed a significant improvement (Sig. 2-tailed < 0.001), while N-Gain analysis indicated an average improvement in the moderate category (0.4028). The study concludes that the integration of Word Wall and Active Learning significantly enhances students’ understanding, participation, and learning outcomes, although effectiveness varies among students. These findings highlight that visual media combined with participatory methods provide a meaningful, engaging, and effective approach to Nahwu learning.